Interaction of macro-management policies to reduce lending growth - Zehri, Chokri; Iben Ammar, Latifa Saleh; Zehri, Fatma (Technological and Economic Development of Economy, 2023)
This paper examines whether capital flow management (CFM) and monetary policies effectively reduce lending growth in emerging market economies (EMEs) in the presence of conventional and unconventional monetary policy actions undertaken by advanced economies. We apply a dynamic panel model with fixed effects to a sample of 24 emerging market economies for 2000–2021 using quarterly data and more continuous variables than in other studies rather than limiting the variability using proxies. Capital controls and macroprudential regulation, as CFM policy tools, moderate lending growth. This effect is particularly shown in countries with tighter monetary conditions. Our main findings highlight the useful role of coordinating CFM and monetary policies. This role stands for both fixed and flexible exchange rate regimes. Lastly, we find capital flow management and monetary policies manage to control lending in normal periods, but their coordination is less effective during crises and high volatility periods.First published online 07 November 2023